An investigation into the use of derivatives by Botswana, Namibia, Zambia and Zimbabwe - Crnkovic, Joseph Richard (Department of Finance and Tax, 2014)
The aim of this paper is to look at derivative usage in Botswana, Namibia, Zambia and Zimbabwe and contrast the findings to surveys done of other countries. There is no evidence of similar studies done on small sub Saharan African countries, so there is no specific literature driven expectations based outcome. One can however draw logical expectations regarding the findings based on the homogenous characteristics of smaller countries (and markets) in the rest of the world and similar studies done on those countries.